The Evangelical Significance of the Healing Miracles in Mark 1: 29-34 in the Providence Delta Baptist Conference - Evwierhurhoma, Silas Akpomejero; Enuwosa, Joseph (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This study investigates the evangelical significance of healing miracles in Mark 1:29–34, with particular reference to the Providence Delta Baptist Conference in Nigeria. It examines the historical and theological background of the Gospel of Mark, scholarly perspectives on Jesus' healing ministry, and evangelical application of biblical healing narratives. Relying on historical, literary, and analytical methods, and drawing from a variety of scholarship and African contextual considerations, this study undergirds the place of healing as a platform for evangelism, a demonstration of Christ's authority, a sign of the gospel message, and a catalyst for discipleship. This research then examines the current practice of healing ministry within the Providence Delta Baptist Conference by focusing on present evangelistic practices, challenges, and opportunities that involve the integration of healing into outreach strategies. Practical models for effective ministries are proposed, such as house-to-house visitation, community healing events, discipleship linkage, and faith-based social projects. Ethical and doctrinal considerations for implementing healing ministry in Nigerian Baptist contexts are also discussed. The study concludes that the healing miracles of Jesus offer profound theological and practical insights for evangelical ministry. Integrating healing into their evangelistic strategies, Nigerian churches can deepen discipleship, engender faith, and expand the gospel's reach while maintaining doctrinal fidelity and ethical integrity. This research contributes to a deeper understanding of holistic ministry, contextualized evangelism, and the integration of healing in African Christianity.